Diálogos sobre educação e tecnologias: configurações do trabalho docente na pandemia - GOMES, André Romão (2022)
The article discusses the vision and correlation of teacher, student and technologies in the teaching and learning process from the perspective of the teacher, in the context of the covid-19 pandemic, taking into account the adaptations and the new structure of the classroom. To analyze the teachers' reports, it was necessary to create a virtual questionnaire through the google forms platform, with 6 objective and 4 subjective questions, aimed at the use of Digital Technologies of Information and Communication in education, where 28 public school teachers contributed. After analyzing the collected information, the relationship between knowledge and pleasure, satisfaction, playing, learning and technological tools is perceived as positively evaluated by teachers. This result confirms how TDICs can help the teacher in the classroom with tools that facilitate the teaching and learning process. However, the need for structural improvements and continuing education for teachers is identified.